In patients undergoing coronary artery bypass grafting is semi-skeletonization superior to pedicled harvesting of the left internal mammary artery?. (25th May 2021) - Maskell, Perry; Berks, Madhavi; Vibhishanan, Jonathan; Harky, Amer
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was, 'in patients undergoing coronary artery bypass grafting is semi-skeletonized harvesting superior to pedicled harvesting of the left internal mammary artery (LIMA) in terms of conduit length, flow, rate of sternal wound infections and post-operative bleeding?'. Altogether, 235 papers were found using the reported search, of which 5 represented the best evidence to answer the clinical question. Three studies were cohort studies and 2 were randomized controlled trials. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. One randomized controlled trial showed superiority with semi-skeletonized harvesting in terms of conduit length ( P < 0.001), flow ( P = 0.004) and diastolic filling ( P = 0.005). Three studies included data on surgical wound infections/mediastinitis, all of which reported n = 0. One randomized controlled trial and 3 cohort studies reported that semi-skeletonized harvesting reduced postoperative bleeding. No studies reported a statistically significant difference in operative time. This review suggests that semi-skeletonized harvesting could possibly be associated with favourable outcomes when compared to pedicled harvesting with respect to graft length and flow, and lower postoperative bleeding, without increasing operative time; although there is insufficient data to compare sternal wound infections or long-term outcomes. In conclusion, the limited evidence base prevents robust informed decision-making when comparing both techniques.